How long-lived is ultrahigh temperature (UHT) metamorphism?: Constraints from zircon and monazite geochronology in the Eastern Ghats orogenic belt, India - Korhonen, Fawna; Clark, Christopher; Brown, M.; Bhattacharya, S.; Taylor, Richard (Elsevier BV, 2013)
Along the coast of Peninsular India, the Eastern Ghats expose a deep crustal section through a composite Proterozoic orogenic belt. To quantify the late Mesoproterozoic–early Neoproterozoic pressure (P)–temperature (T)–time (t) evolution of the Eastern Ghats Province, new SHRIMP U–Pb zircon and monazite age data from multiple localities are reported and integrated with the results of phase equilibria modelling. Samples of residual granulite, migmatite and enderbite yield a spread of weighted mean 207Pb/206Pb zircon and monazite ages between ca 970 and ca 930 Ma. Based on ranges of spot ages from several samples, the late prograde to peak ultrahigh temperature (UHT) metamorphism (counter-clockwise evolution (CCW) to T >950 °C at >P8 kbar) and initial cooling is interpreted to have occurred between ca 1130 and ca 970 Ma. Regionally extensive enderbite and charnockite magmas were emplaced into the hot, suprasolidus crust around the time of peak metamorphism. For the residual granulites and migmatites the retrograde P–T–t path is characterized by close-to-isobaric cooling to the variable but elevated solidi for different samples. Weighted mean ages between ca 970 and ca 930 Ma in several samples are interpreted to record the timing of crystallization of melt trapped by the percolation threshold in each of these samples.Two additional weighted mean ages of ca 980 Ma (from Korhonen F.J., Saw, A.K., Clark, C., Brown, M., Bhattacharya, S., 2011. New constraints on UHT metamorphism in the Eastern Ghats Province through the application of phase equilibria modelling and in situ geochronology. Gondwana Research 20, 764–781) extend this range back in time by 10 My. The variability in the calculated weighted mean ages across the region is interpreted to be due mainly to differences in the temperature of the elevated solidus from sample to sample, suggesting a slow cooling rate of ~1 °C/My during the retrograde stage of this long-lived UHT metamorphism. These results demonstrate that the Eastern Ghats Province sustained UHT conditions (T>900 °C) for ≫50 My, and perhaps for as long as 200 Ma from ca 1130 to 930 Ma, during a single CCW tectono-metamorphic event.